To solve the mathematical problem involving absolute value, let's break it down into smaller steps:
Step 1: Calculate the expression inside the absolute value brackets.
3 - 1 2/3 * -6 1 + 2
First, convert the mixed number, 1 2/3, into an improper fraction:
1 2/3 = (3*1 + 2)/3 = 5/3
Now, substitute the new fraction into the expression:
3 - 5/3 * -6 1 + 2
Next, perform the multiplication and addition/subtraction within the expression:
3 - 5/3 * -6 = 3 + 5/3 * 6 = 3 + 30/3 = 3 + 10 = 13
So the expression inside the absolute value brackets simplifies to 13.
Step 2: Evaluate the absolute value of 13.
|13| = 13
Therefore, the solution to the mathematical problem is 13.
Solve the mathematical problem involving absolute value 3 - 1 2/3 * -6 1 + 2
1 answer